2019
DOI: 10.1088/1742-6596/1317/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of entrepreneurial motivations in tourism based on local resources and creative economy in nagari salayo of west sumatra

Abstract: The purpose of this study is to analyze the entrepreneurial motivations in tourism based on local resources and creative economy in Nagari Salayo of West Sumatra in developing this area into a cultural and creative based tourist destination. The sixty beginner entrepreneurs are involved in this research in community services, where their entrepreneurial motivations are measured by an entrepreneurial motivation scale of the questionnaire and analyzed by using path analysis in determining the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Although health and disaster most likely to sharpen tourist's travel risks for vulnerable traveler [3,28,29], our study reveal that travelling was identified as an activity that stimulate the positive emotions and support to improve traveller's mental health issue. This show that travelling shape tourist's positive emotion such as in a short vacation [20,30]. This finding also reinforce study of Vázquez, et al [31] who found that the positive reaction and emotion were still attached in affected people, despite the devastating negative events (e.g.…”
Section: Conclusion Implication and Future Studysupporting
confidence: 77%
“…Although health and disaster most likely to sharpen tourist's travel risks for vulnerable traveler [3,28,29], our study reveal that travelling was identified as an activity that stimulate the positive emotions and support to improve traveller's mental health issue. This show that travelling shape tourist's positive emotion such as in a short vacation [20,30]. This finding also reinforce study of Vázquez, et al [31] who found that the positive reaction and emotion were still attached in affected people, despite the devastating negative events (e.g.…”
Section: Conclusion Implication and Future Studysupporting
confidence: 77%
“…However, based on theory, the unique place, the more people want to make a return visit. The more visitors, the more creative the economy of the local people [26].…”
Section: The Effect Of Artificial Attraction On West Sumatra's Tourismentioning
confidence: 99%
“…Most tourism studies are exploratory-based research papers in nature (i.e., Devianto, Ridho, Maryati, & Lenggogeni, 2019;Filimonau & Mika, 2019;Mason, Augustyn, & Seakhoa-King, 2010;Nunkoo & Ramkissoon, 2011). There are many development research theories, such as a new scale development in tourism study (for instance, Lenggogeni, Ritchie, & Slaughter, 2019), which is often applied in the complex multiple regression-based research framework (Lenggogeni, 2015;Lenggogeni & Saito, 2018).…”
Section: Structural Equation Modelling In Tourism Research and Theorymentioning
confidence: 99%